Video Classification using Fractional Fourier Transformed Content of Video - Madhura M, Kalbhor; Sudeep D, Thepade (International Journal of Computer Sciences and Engineering, 2015)
Advanced technology has resulted in drastic growth of multimedia data. In day to day life huge amount of multimedia data is generated an uploaded over web. Storing this multimedia data has become a challenging task. Storing the data in video format efficiently and retrieving it accurately has become important. If the data is appropriately classified under different categories and then stored, it can be retrieved faster. In this paper a novel video classification techniques has been proposed to classify the videos. Transform domain has the property of energy compaction that helps to figure out the important data in the video and neglect the least important data. Thus the proposed techniques uses the Fourier transformed video content as the attributes for classification process. Twelve different classification algorithms are used and six fractional portions of transformed content forming the feature vectors of six different sizes are experimented. With the proposed technique highest classification accuracy of 89.16% is obtained.